2022
DOI: 10.3389/fsurg.2022.926745
|View full text |Cite
|
Sign up to set email alerts
|

A New Nomogram Model for Predicting 1-Year All-Cause Mortality After Hip Arthroplasty in Nonagenarians With Hip Fractures: A 20-Year Period Retrospective Cohort Study

Abstract: BackgroundChina has become an ageing society and as it continues to age, it will face an increasing number of hip fractures in nonagenarians. However, few preoperative assessment tools to determine the postoperative mortality risk in nonagenarians with hip fracture were available. The aim of this study was to identify all-cause mortality risk factors after hip arthroplasty in nonagenarians with hip fractures and to establish a new nomogram model to optimize the individualized hip arthroplasty in nonagenarians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In general, arthroplasty is associated with a relatively greater severity of surgical trauma and increased blood loss, even when performed by proficient surgeons, compared to PFNA. Anemia caused by blood loss and bleeding is associated with postoperative mortality and morbidity in the elderly 7,44 . Preventing or timely correcting anemia is vital for this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, arthroplasty is associated with a relatively greater severity of surgical trauma and increased blood loss, even when performed by proficient surgeons, compared to PFNA. Anemia caused by blood loss and bleeding is associated with postoperative mortality and morbidity in the elderly 7,44 . Preventing or timely correcting anemia is vital for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia caused by blood loss and bleeding is associated with postoperative mortality and morbidity in the elderly. 7 , 44 Preventing or timely correcting anemia is vital for this patient population. In the present study, the blood loss, blood transfusion, and transfusion rates during the surgical procedure in the bipolar HA group were significantly higher than those in the PFNA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the stress of surgical trauma can cause heart failure, arrhythmia, and respiratory dysfunction, endangering the life of patients. 49 Nomogram, as a prognosis statistic model, makes prediction easier and more convenient 50,51 and has higher accuracy and convenience than other models. 52 We included the risk factors found by logistic analysis into the nomogram model, which was successfully validated using the ROC curve and Hosmer-Lemeshow test.…”
Section: Risk Factors Of Mortality After Artificial Hip Arthroplastymentioning
confidence: 99%
“…Surgeons and patients are often hesitant to proceed with surgery due to concerns over advanced age and pre-existing comorbidities that may lead to postoperative complications and mortality 9 , 10 . While certain experts 11 , 12 particularly regarding the survival results, have indicated advantages, there is concern 13 17 among certain research that high proportion of complication rates after surgery were observed whether they had been treated surgically or conservatively. Due to multiple comorbidities, leaving hip fractures untreated can result in 1-year mortality rates of over 60% for nonagenarians and centenarians, as well as other adverse outcomes including longer length of hospital stay (LOS), frequent readmissions, and increased rates of mortality and complications 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%